O‘zbekistonda sug‘orish tizimlari va yer melioratsiya jarayonlari tarixidan (1950-1990-yillar) - Mamajanov, A.A (SCIENCE and SOCIETY, 2025)
The article analyzes the policy of the centre of the further strengthening mono cultural clap in Uzbekistan that in undertaken measures on building of large irrigation canals and pumping stations in the Republic on the basis of archival sources and historical materials. Therefore, the process of reclamation and irrigation of lands in the country as well as, organization of districts and state farms in these areas specialized to cotton - growing on the principles of cotton monopoly policy of the Soviet government and increase of provision of cotton to the centre and its negative results are elucidated with the help of main historical sources. Besides, in the research the author studied the reclamation of virgin lands in Uzbekistan and the history of state farms organized in the new reclaimed lands.
Keywords: agriculture; cotton monopoly; irrigation system; land reclamation; soviet government; reconstruction; siphon; Uzbekistan; virgin lands; water reservoir